Energetic Status Modulates Facultative Migration in Brown Trout (Salmo trutta) Differentially by Age and Spatial Scale - Shry, Samuel J.; McCallum, Erin S.; Alanärä, Anders; Persson, Lo; Hellström, Gustav (Frontiers in Ecology and Evolution, 2019)
Fish display a remarkable diversity in juvenile migration strategies and behaviour. Intra-species variation in migration can be considerable, and understanding the driving force of such variation is important for effective management and conservation of migratory fish. In facultative migratory species, such as many salmonid fish, energetic status is known to affect migration strategy and behaviour. However, we currently lack a full understanding of how energetic status affects juvenile development and migration over different environmental contexts. In this study, we examined the effect of energetic status on juvenile migration initiation and migratory behaviours in one and two year old brown trout (Salmo trutta). By manipulating feeding regimes, we created a large variation in trout energetic status (using condition factor as a proxy). We then studied behavioural changes in migration in both a controlled environment (large-scale migration pools) as well as a natural river system using both passive integrative transponder tags (PIT-tags) as well as acoustic telemetry tags. In the laboratory setting, one year old trout with higher energetic status were more likely to initiate migration and migrated faster. For two year old trout, energetic status did not affect the initiation of migration (the large majority migrated), but high energetic status fish migrated faster. In a small-scale natural creek system, few age one fish migrated (11 %); however, these few migrators were within the upper range of energetic status. In two year old trout, a high percentage became migrants (79 %), and those with higher energetic status migrated at a faster speed. In a large-scale river system, successful downstream seaward migration for two year olds was low (9 %) and independent of energetic status. Our findings provide valuable data for fisheries management because we show that age at release and energetic status prior to release can impact migration initiation and behaviours. Our findings also indicate that migration measured in the laboratory may over estimate migration in the wild, especially for younger, age one fish. More broadly, this work advances our understanding of this complex life history stage and the mechanisms involved in the initiation, behaviour, and survival of migrating brown trout.